Pelatihan Karang Taruna Desa Sinar Bhakti : Mengelola Instagram untuk Layanan Masyarakat - Aimar Aqil Manaf; Yaz Montis Hidayat; Muhammad Gilang Anugrah; Nyimas Rani Pertiwi; Rosmala Dewi (Fakultas Teknik Universitas Maritim AMNI Semarang, 2025)
This training aims to empower the Youth Organization of Sinar Bhakti Village to optimize Instagram as a medium for information dissemination and community services. The main problem identified is the lack of understanding and skills among Youth Organization members in effectively utilizing social media to support local activities and community needs. The training methods included material delivery through presentations, group discussions, and hands-on practices with a participatory approach. Participants were trained to create relevant, engaging, and informative content and learned professional techniques for managing Instagram accounts. The results of the training revealed that participants gained a better understanding of digital communication strategies, such as utilizing Instagram features to disseminate information, promote village activities, and enhance community interaction. Participants also demonstrated increased confidence in managing social media as a primary means of communication with the community. Overall, this training successfully enhanced the capacity of the Youth Organization to leverage digital technology for empowering local communities.